A proposal for an information programmer to investigate some of the problems of secondary education students in Algeria and treat them. Analytical statistical study of 400 male and female students from the second year of high school in Algeria, with a cli - Zoubida MAHI; Mohamed MEKI (Social Sciences Journal, 1970)
Teenagers suffer many adaptability issues that require elderly attention and assistance to beovercome, as evidenced by the current study whose aim was to look into issues afflicting secondyear secondary pupils, classify them by the importance of their impact and then, find the necessarysolutions. The conclusions of the study were, in its clinical part, a reclassification of the problemssuffered by the study cases as well as a reduction of their impact – which is testimony to theeffectiveness of the treatment – and, in its analytical and statistical part, assessment of the scale ofeach problem’s impact on pupils, arranged in decreasing order according to their effect on them,where study samples emotional problems came up top of current school issues while family andhealth problems were last.